2022
DOI: 10.3389/fenvs.2022.967050
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, institutional quality, economic growth and CO2 emission in OECD countries: An analysis with GMM and quantile regression

Abstract: This research used the dynamic panel model and QR (Quantile Regression) to examine the effect of globalization (GB), Institutional Quality (IQ), Economic Growth (EG), Electricity Consumption (EC), and Renewable Energy (RE) consumption on Carbon dioxide (CO2) emission from 1991 to 2018 in thirty-six (OCED) countries. Panel unit root tests have been employed to examine the stationarity of the study variables; the results, which included the Harris and Tzavalis (Journal of econometrics, 1999, 91 (2), 201–226) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
2
3
0
Order By: Relevance
“…The findings are consistent with theoretical and empirical expectations, and they support the notion that in the long run, CO 2 emissions move in tandem with CGI and other control variables augmented in the study. Additionally, our results are consistent with the findings of Goel et al 86 , Lau et al 87 , and Fatima et al 88 , who also documented significant cointegrations between the predictors of institutional quality and CO 2 emissions. While cointegrated vectors suggest that CGI and other control variables affect CO 2 emissions differently across all panels, they also trigger delving into the scale and magnitude of the effects of CGI and control variables on the subject matter.…”
Section: Resultssupporting
confidence: 93%
“…The findings are consistent with theoretical and empirical expectations, and they support the notion that in the long run, CO 2 emissions move in tandem with CGI and other control variables augmented in the study. Additionally, our results are consistent with the findings of Goel et al 86 , Lau et al 87 , and Fatima et al 88 , who also documented significant cointegrations between the predictors of institutional quality and CO 2 emissions. While cointegrated vectors suggest that CGI and other control variables affect CO 2 emissions differently across all panels, they also trigger delving into the scale and magnitude of the effects of CGI and control variables on the subject matter.…”
Section: Resultssupporting
confidence: 93%
“…Consequently, this leads to the implementation of environmentally friendly policies. The findings of the research align with results of previous studies devoting developed countries, such as Anwar & Malik (2022) in the case of G-7 countries, Li et al (2022) in the case of Canada, Fatima et al (2022) in the case of OECD countries, Khan et al (2022) in the case of G-7 countries, which found a negative influence of institutional quality. Furthermore, we observed a positive impact of income, as measured by real GDP per capita on CO2 emissions in Canada.…”
Section: Empirical Results and Discussionsupporting
confidence: 88%
“…They concluded the negative impact of control of corruption as a proxy of institutional quality on CO2 emissions by utilizing the GMM model. Besides, Ali et al (2019) in the case of 47 developing countries, Danish & Ulucak (2020) in the case of 18 Asia-Pacific Economic Cooperation countries, Anwar & Malik (2022) in the case of G-7 countries, Abd Razak et al (2021) in the case of Malaysia, Mehmood (2022) in the case of 11 countries, Xaisongkham & Liu (2022) in the case of developing countries, Bakhsh et al (2021) in the case of Asian countries, Karim et al (2022) in the case of 30 Sub-Saharan African, Li et al (2022) in the case of Canada, Fatima et al (2022) in the case of OECD countries, Khan et al (2022) in the case of G-7 countries revealed a negative effect of institutional quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Political reforms can support increased funding and attention to environmental conservation efforts and lead to improvements in waste management and recycling systems [ 39 , 61 ]. Reformed governments can invest in green infrastructure, such as public transportation, urban planning that promotes green spaces, and sustainable construction practices [ 62 ]. Green infrastructure can reduce the ecological footprint of cities and improve the quality of life for citizens [ 40 ].…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%